2005
DOI: 10.3201/eid1110.050125
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistantStaphylococcus aureus, Western Australia

Abstract: Endemic MRSA persists in Western Australia despite control measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…Most strains of HA-MRSA fall into five broad lineages that are responsible for the majority of infections worldwide (38). Infections due to CA-MRSA can be seen in hospital settings, with occasional major outbreaks (4,7), while HA-MRSA strains are also able to circulate within communities (32).…”
mentioning
confidence: 99%
“…Most strains of HA-MRSA fall into five broad lineages that are responsible for the majority of infections worldwide (38). Infections due to CA-MRSA can be seen in hospital settings, with occasional major outbreaks (4,7), while HA-MRSA strains are also able to circulate within communities (32).…”
mentioning
confidence: 99%
“…One disadvantage of attempted decolonization is the development of resistance to the agents used. Mupirocin resistance has been documented in several studies (131)(132)(133)(134), usually associated with prolonged use or repeated courses of mupirocin. In Canada, Mulvey et al (109) have reported mupirocin resistance rates of up to 50% in community isolates on the prairies.…”
Section: Decolonizationmentioning
confidence: 99%
“…In Canada, Mulvey et al (109) have reported mupirocin resistance rates of up to 50% in community isolates on the prairies. Limiting its use to a maximum course of five to 10 days and ensuring a minimum time period of one month between recurrent use are strategies that have been found to be effective in preventing the emergence of mupirocin resistance (133,134).…”
Section: Decolonizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[64][65][66] Similar low rates in western Australia have also been attributed to long-standing policies of rigorous screening and isolation. 67 The literature is contradictory about the benefit of masks in the prevention of cross-transmission of S. aureus, 49 apart from their role in preventing droplet transmission in the setting of a patient colonized with MRSA with respiratory symptoms. 68 Vancomycin-resistant enterococci does not colonize the respiratory tract, and there is no role for masks in preventing cross-transmission.…”
Section: Barrier Precautionsmentioning
confidence: 99%